Automated determination of auroral breakup during the substorm expansion phase using all‐sky imager data. Issue 2 (22nd February 2014) - Murphy, Kyle R.; Miles, David M.; Watt, Clare E. J.; Rae, I. Jonathan; Mann, Ian R.; Frey, Harald U.
Abstract This paper describes a novel method for quantitatively and routinely identifying auroral breakup following substorm onset using the Time History of Events and Macroscale Interactions during Substorms all‐sky imagers. Substorm onset is characterized by a brightening of the aurora that is followed by auroral poleward expansion and auroral breakup. This breakup can be identified by a sharp increase in the auroral intensity i(t) and the time derivative of auroral intensity i(t). Utilizing both i(t) and i'(t), we have developed an algorithm for identifying the time interval and spatial location of auroral breakup during the substorm expansion phase based solely on quantifiable characteristics of the optical auroral emissions. We compare the time interval determined by the algorithm to independently identified auroral onset times from three previously published studies. In each case the time interval determined by the algorithm is within error of the onset independently identified by the prior studies. We further show the utility of the algorithm by comparing the breakup intervals determined using the automated algorithm to an independent list of substorm onset times. We demonstrate that 50% of the breakup intervals characterized by the algorithm are within the uncertainty of the times identified in the list. The quantitative description and routine identification of an interval of auroral brightening during the substorm expansion phase provides a foundation for unbiased statistical analysis of the aurora and to probe the physics of the auroral substorm and identify the processes leading to auroral substorm onset.